2009
DOI: 10.2353/ajpath.2009.080954
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Pulmonary Fibrosis Identifies Twist1 as an Antiapoptotic Molecular “Rectifier” of Growth Factor Signaling

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive and typically fatal lung disease. To gain insight into IPF pathogenesis, we performed gene expression profiling of IPF lungs. Twist1, a basic helix-loop-helix protein, was found among the most consistently and highly up-regulated genes and was expressed in nuclei of type II epithelial cells, macrophages, and fibroblasts in IPF lungs. We studied the function of Twist1 in fibroblasts further, because they are the major effector cells in this disease and persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 51 publications
(51 reference statements)
8
51
1
Order By: Relevance
“…As Yang and colleagues first reported that Twist1 is a critical player in cancer metastasis (16), most studies focused on Twist1's role in cancer cells (22)(23)(24), with little attention paid to its possible role in the tumor microenvironment, including CAFs. In contrast to rare expression of Twist1 in adult normal fibroblasts, Twist1 is frequently and strongly expressed in embryonic fibroblasts (9,11,25) and pathologic fibroblasts in idiopathic pulmonary fibrosis (26,27) and desmoid tumor (28). Bridges and colleagues (26) reported that Twist1 enhanced survival and accumulation of fibroblasts in fibrotic lung disease, which is consistent with results of our current study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As Yang and colleagues first reported that Twist1 is a critical player in cancer metastasis (16), most studies focused on Twist1's role in cancer cells (22)(23)(24), with little attention paid to its possible role in the tumor microenvironment, including CAFs. In contrast to rare expression of Twist1 in adult normal fibroblasts, Twist1 is frequently and strongly expressed in embryonic fibroblasts (9,11,25) and pathologic fibroblasts in idiopathic pulmonary fibrosis (26,27) and desmoid tumor (28). Bridges and colleagues (26) reported that Twist1 enhanced survival and accumulation of fibroblasts in fibrotic lung disease, which is consistent with results of our current study.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast to rare expression of Twist1 in adult normal fibroblasts, Twist1 is frequently and strongly expressed in embryonic fibroblasts (9,11,25) and pathologic fibroblasts in idiopathic pulmonary fibrosis (26,27) and desmoid tumor (28). Bridges and colleagues (26) reported that Twist1 enhanced survival and accumulation of fibroblasts in fibrotic lung disease, which is consistent with results of our current study. Bacac and colleagues (28) reported that Twist1 is highly expressed in desmoid tumors (neoplastic myofibroblastic lesions) compared with nodular fasciitis (nontumorous proliferation of fibroblasts).…”
Section: Discussionsupporting
confidence: 83%
“…end products, as potential regulators of lung fibrosis (6)(7)(8)(9)(10)(11)(12). Additionally, we and others have identified gene expression patterns that distinguish IPF from hypersensitivity pneumonitis, variants of disease that characterize distinct patterns of progression and characterize patients with pulmonary hypertension (9,(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…The demonstration of an increase in Twist1, a transcription factor that plays the role of master regulator of these processes, is consistent with the suggestive role of EMT in IPF. 23,24 The contribution of EMT to IPF, however, is an active topic of debate. 25,26 Regardless, the contribution of TGF-in fibrotic lung disease is not in question -it is both a target and an inducer of Twist1 and Twist1 is regulated through a feed-forward mechanism contributed both by Twist1 itself and nuclear factor-B, induced by inflammatory signals.…”
Section: Ipf: Fibrosis As An Example Of Unremitting Dysregulated Matrmentioning
confidence: 99%